Analisis Implementasi SOP Medical tourism dalam Peningkatan Daya Saing RS BIMC Siloam Nusa Bali - Cokorda Gede Bagus Pradnyana Sanjaya; Rian Andriani; Achmad Dheni Suwardhani (Yayasan Literasi Sains Indonesia, 2025)
Medical tourism is the activity of patients traveling across countries to obtain better or more affordable medical services. Since 2012, Bali International Medical Center (BIMC) Siloam Nusa Dua Hospital has focused on cosmetic surgery and dental tourism services through the CosMedic Center. After the Covid-19 pandemic, patient visits decreased by 70%, while other medical tourism centers in Bali have grown rapidly, thus requiring BIMC to increase its competitiveness. This study aims to analyze the implementation of medical tourism services in improving hospital competitiveness. This study uses a qualitative descriptive approach with an in-depth interview method with key informants. The results show that at the pre-hospital stage, 24-hour service is not optimal and patient interest in choosing a complete package (transportation, accommodation, tour) is still low. At the hospital service stage, there is no special inpatient room for medical tourists, while the post-hospital stage runs according to the SOP. Collaboration with the Travel Agency (BPW) revealed the limitations in the quality and quantity of certified medical tourism guides. In conclusion, the implementation of the SOP for medical tourism at BIMC Siloam Nusa Dua has been running according to Permenkes No. 76 of 2015, but to strengthen competitiveness, it is necessary to improve 24-hour services, strengthen promotion and branding, develop special inpatient room facilities, and improve the quality and number of medical tourism guides. These findings are expected to be the strategic basis for developing sustainable medical tourism in Bali.